2000
DOI: 10.2337/diabetes.49.12.2208
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine exposure to diabetes conveys risks for type 2 diabetes and obesity: a study of discordant sibships.

Abstract: Intrauterine exposure to diabetes is associated with an excess of diabetes and obesity in the offspring, but the effects of intrauterine exposure are confounded by genetic factors. To determine the role of the intrauterine diabetic environment per se, the prevalence of diabetes and the mean BMI were compared in siblings born before and after their mother was recognized as having diabetes. Nuclear families in which at least one sibling was born before and one after the mother was diagnosed with type 2 diabetes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
750
5
21

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,149 publications
(795 citation statements)
references
References 27 publications
19
750
5
21
Order By: Relevance
“…Studies of siblings among Pima Indians suggest that in that population the association of maternal gestational hyper- glycaemia with later offspring obesity is likely to be explained by specific intrauterine effects in addition to any genetic or behavioural mechanisms [10]. While some mothers in the ALSPAC study did have more than one live birth during the 2-year recruitment period, numbers of siblings within the study sample are too small to undertake within-sibling analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of siblings among Pima Indians suggest that in that population the association of maternal gestational hyper- glycaemia with later offspring obesity is likely to be explained by specific intrauterine effects in addition to any genetic or behavioural mechanisms [10]. While some mothers in the ALSPAC study did have more than one live birth during the 2-year recruitment period, numbers of siblings within the study sample are too small to undertake within-sibling analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of Pima Indians, a marked excess in the risk of obesity has been found at all ages from birth to 20 years in offspring born to mothers who had diabetes during their pregnancy compared with the offspring of either mothers who developed diabetes later in their lives or those who never developed diabetes [7][8][9]. In a nuclear family study, also conducted in Pima Indians, obesity was greater among offspring born after the mother had been diagnosed with diabetes than in their sibs born before their mother's diagnosis [10]. These differences were not found in siblings born before and after the father was diagnosed with type 2 diabetes, suggesting that, in a population at high risk of obesity and diabetes, exposure to maternal diabetes in utero has long-term effects on the offspring that are in addition to genetic and shared familial factors.…”
Section: Introductionmentioning
confidence: 99%
“…In a vicious cycle prenatal development in a diabetic milieu favours development of diabetes later in life (11) . Alterations in maternal nutrition may induce long-term metabolic consequences in offspring.…”
Section: Developmental Origin Of Adult Health and Diseasementioning
confidence: 99%
“…4 Furthermore, maternal overweight before pregnancy and maternal diabetes are associated with offspring obesity, possibly due to genetic effects, but perhaps also because of the intrauterine environment. [5][6][7][8] This transgenerational association implies that the maternal obesity may, by its effect on the offspring, induce a viscous cycle accelerating the obesity epidemic in successive generations. 7,9,10 Such acceleration has been observed in the stepwise development of the obesity epidemic in Denmark, where the second phase was much steeper than the first phase.…”
Section: Introductionmentioning
confidence: 99%